Peculiarities of Foreign Language Inclusions in L.N. Tolstoy’s “Mournful List of Mental Patients of the Yasnopolyansky Hospital” - Anna A. Shcherbinina (Studia Litterarum)
The article is devoted to the study of L.N. Tolstoy’s multilingualism on the basis of unexplored from a scientific point of view “Mournful list…” The author of the article focuses on the peculiarities of the use, the meaning and the functions of foreign language inclusions in this work by Tolstoy. The article analyzes word formation, including the combination of different languages in phrases or words. In this regard, problems arise in identifying languages in foreign inclusions and choosing a translation based on authentic grammatical forms. The author of the article proposes possible solutions in each case. The appeal to manuscripts and various publications of the “Mournful list…” contribute to the restoration of the original spelling of some foreign language inclusions and the definition of the meaning nearest to the author’s intention. The research also appeals to the diaries of the writer and the memoirs of his family members. The ideological content of the “Mournful list…” is interconnected with the works of L.N. Tolstoy of the 1880s, which are identical in theme and problematic. Thus, the paper clearly shows the value of the “Mournful list…” not only for the biography, but also for the work of L.N. Tolstoy.